Dinamika Komunikasi Digital: Tren, Tantangan, dan Prospek Masa Depan - Diva Andzani; Irwansyah (Syntax Corporation Indonesia, 2023)
This study explores the dynamics of digital communication, focusing on trends, challenges, and future prospects. The research method used is a literature review, which involves the identification, selection, analysis, and synthesis of relevant information sources. The research findings reveal that current trends in digital communication include increased use of social media, the dominance of instant messaging applications, and changes in video content consumption. Social media has enabled us to expand our social networks globally but has also given rise to issues such as digital social isolation and the pressure to constantly share happiness. Instant messaging applications have brought efficiency to communication but also pose challenges such as distractions and privacy concerns. The consumption of video content has transformed how we consume entertainment and art, creating trends like